Psychoeducation of the Nigeria Population on Knowledge of Substance Abuse, Drug Addiction and Regular Medical Check-Up - Zakariah, Danladi; Akafa, Tensaba Andes; Akafa, Vika Tensaba; Oladele, Gloria Omonefe; Iseko, Kingsley Iyoko; David, Izam Emmanuel; Ujah, Oche Williams; Gadin, Ndentang Ira (Darul Yasin Al Sys, 2024)
This paper aims to enhance psychoeducation among the Nigerian population regarding substance abuse, drug addiction, and the importance of regular medical check-ups. Substance abuse and drug addiction are significant contributors to various medical health conditions and mental disorders within the Nigerian populace. Many of these conditions could potentially be prevented or managed effectively if early detection of abnormal neurotransmitter changes in the brain was facilitated through routine medical examinations. This study highlights the alarming scarcity of knowledge and poor attitudes towards substance abuse, drug addiction, and regular medical check-ups in Nigeria, as evidenced by empirical data from psychiatric research. Such deficiencies hinder individuals from making informed health decisions and recognizing risk factors associated with unhealthy lifestyles. According to the World Health Organization, as well as the International Classification of Diseases (ICD-11) and the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), substance abuse and drug addiction are classified as diseases that require treatment, akin to conditions such as diabetes, cancer, heart disease, and HIV. In light of this, the paper calls on the government, as well as the management of healthcare institutions, clinical psychologists, and other healthcare professionals, to prioritize intensive psychoeducation initiatives. These initiatives should focus on raising awareness about the dangers of substance abuse and drug addiction, as well as preventative measures. Moreover, the government and health institutions should collaborate with philanthropists to establish more psychiatric hospitals and rehabilitation centre, providing testing equipment and medications at subsidized rates across all healthcare levels. This would enable individuals struggling with substance abuse and addiction to access necessary services, gain insights into their health status, improve their overall well-being, and alleviate the catastrophe financial burdens faced by their families and loved ones. In conclusion, this paper emphasizes the urgency of addressing these issues and provides actionable recommendations for creating a more informed and supportive environment for those affected by substance abuse and addiction.